Religious Effect-Based Education Model in Pesantren on Handling Drug Cases - Subiyantoro; Sulistyo, Heru; Solikhin, Muhammad; Nurdin, Muh. Nur Islam (LETIGES, 2024)
The handling of drug cases has developed with the presence of Islamic boarding schools that specifically focus their educational orientation on handling this case. The involvement of Islamic boarding schools in handling drug offenders indicates the development of a rehabilitation process that has only been played by the National Narcotics Agency. This study will reveal the religious effect-based education model in handling drug cases in Ar-Rahman Palembang and Suryalaya Tasikmalaya Islamic boarding schools with an empirical qualitative descriptive approach. Data collection uses in-depth interviews, observation, and documentation which are then analyzed using Spradley's inductive model technique which begins with compiling research questions, then determining research propositions, research analysis units, data linkage logic with propositions, criteria for interpreting findings, and finally presenting research results. The research findings show three essential things. First, overcoming drug offenders is carried out through five stages, namely client acceptance, program orientation, primary program, re-entry program, and complete program. Second, client healing is carried out with therapist techniques with religious methods, Focus Group Discussions, narcotic animus, as well as medical and psychological. Third, the implications are oriented towards three main aspects: behavioral and mental changes, awareness to stop consuming drugs, and the emergence of obedience in worship. In line with that, this study has limitations because it only uses descriptive analysis of limited data. Therefore, further studies with more comprehensive data coverage are expected.